Minkowski type problems for convex hypersurfaces in hyperbolic space - Gerhardt, Claus (Arxiv, 2006)
We consider the problem F=f(v) for strictly convex, closed hypersurfaces in hyperbolic space and solve it for curvature functions F the inverses of which are of class (K*)
Gesehen am 26.06.2017